Environmental Effect on Growth and Yield Parameters of Ten Kenaf Varieties (Hibiscus cannabinus L.) in Erbil. - Rabar Fatah Salih; Nawzad Ali Qader (Zanco Journal of Pure and Applied Sciences, 2020)
Differences between growth and yield parameters of ten kenaf varieties were investigated to evaluate and determine the best variety to cultivation at Kurdistan environment. For the first time seeds of ten kenaf varieties were planted in field of Grdarasha in College of Agricultural Engineering Sciences, Salahaddin University – Erbil, Kurdistan. The experiment was arranged using four replicates in Randomized Complete Block Design. Date of flowering, plant height, stem diameter, fresh stem, fresh bast and fresh core yield were measured. Variety FH-952 had the highest value of plant height (340 cm), followed by 4383 variety (310 cm). Despite that, the highest values of other growth and yield parameters such as stem diameter, fresh stem, fresh bast and fresh core yield were recorded on HC 95 variety which was (25.1 mm, 175.0, 41.2 and 134.5) t/ha respectively. Significant results of characteristics from this current study display that, some varieties of kenaf will be selected for replanting since it noted to have high ability to adaptation with Kurdistan environment condition